Amphetamine Positive Urine Toxicology Screen Secondary to Atomoxetine. (30th January 2013) - Fenderson, Joshua L.; Stratton, Amy N.; Domingo, Jennifer S.; Matthews, Gerald O.; Tan, Christopher D.
Abstract : The aim of this paper is to report the first case of atomoxetine leading to false-positive urine drug screen. An otherwise healthy 27-year-old female with a history of attention deficit hyperactivity disorder (ADHD) treated with atomoxetine had an acute onset tonic-clonic seizure. On arrival to the hospital, a urine toxicological drug screen with immunochemical cloned enzyme donor immunoassay (CEDIA) was performed. Results were positive for amphetamines; however, the presence of these substances could not be confirmed with urine gas chromatography-mass spectrometry (GC-MS). She denied any illicit drug use, herbal medications, or supplements, and her other prescription medications have not been previously known to cause a false-positive result for amphetamines. While stimulant treatments for ADHD could certainly result in a positive result on urine screen for amphetamines, there have been no reports of false-positive results for amphetamines secondary to patients using atomoxetine. We implicate atomoxetine, and/or its metabolites, as a compound or compounds which may interfere with urine drug immunoassays leading to false-positive results for amphetamines CEDIA assays.